Intermammary Pilonidal Sinus and Surgical Treatment: Our Clinical Experience - Ozkan, Zeynep; Bozdağ, Ahmet; Akyol, Hadice; Bozan, Mehmet Bugra; Kement, Metin (My University, 2022)
Objective: Pilonidal sinus disease is characterized by chronic inflammatory and granulomatous epithelial tract, usually in the sacrococcygeal area. It is rarely seen in other regions of \rthe body. In this study, we aimed to report our patients with intermammary pilonidal sinus \r(IMPS) and to present the flap operation technique applied to these patients.\rMethods: A total of nine patients who applied to the general surgery clinic between the \ryears 2010 and 2019 for the treatment of IMPS were evaluated retrospectively. Demographic \rcharacteristics of patients, time of onset of the complaints, the length of the sinus tract, the \rtreatment, and the presence of any recurrences were collected by reviewing the hospital \rrecords and calling the patients by phone. In the patients presenting with abscesses, drainage \rwas performed and antibiotic treatment was given to the patients. A standard sinus excision \rwas followed by the closure with a bilateral subcutaneous flap.\rResults: A total of nine female patients were included in the study. All patients were females \rbetween ages 15 and 28 years with a mean age of 19.2±3.4 years. The presenting complaints \rof all patients were intermittent drainage in the intermammary area, the formation of openings, and sometimes pain. The mean length of the sinus was 4.1±0.7 cm. No complications \rand complaints were seen in the patients in the postoperative period.\rConclusion: IMPS is a disease of young women and is curable with surgery. The patients are \rsuccessfully and safely treated with the flap method.
Keywords: Cerrahi